PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK DAN INQUIRY TERBIMBING TERHADAP KEMAMPUAN LITERASI SAINS BERDASARKAN KEMANDIRIAN BELAJAR: Studi Eksperimen dengan menerapkan pembelajaran berbasis STEM - Lestari, Hana (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
The purpose of this reasearch are knowing effect of Self directed learning, PJBL model and Guided Inquiry to science literacy abilities. This study was conducted at SMA Taruna Andigha and SMA Bina Insani in April-May 2018. Design of this research is post-test only experiment and control group design. The method that used on this research was quasi experiment. Experiment class was treated by PJBL model, while control class was treated by Guided Inquiry model. This instruments consist questionnaire of self directed learning and science literacy abilities test. The instruments have been valid and reliable. Analysis data used by Anova 2 ways design (2x2 factorial). The result show that: 1) The ability of science literacy of student who are given PJBL model higher than the students who given Guided inquiry models. (2) There is an enhancement of science literacy of students effected by self directed learning and learning models. (3) The ability of science literacy of students with high self directed learning who given treatment PJBL model is higher than the students who are given Guided inquiry model. (4) There is no significant difference the abiility of science literacy between students low self directed learning who given treatment by PJBL model and students who are given treatment by Guided inquiry model.